Unveiling The Dynamics of Internal and External Management on Public Satisfaction: Insights from Public Service Malls - M. Hidayat Panuntun Muslim; Lanin, Dasman; Frinaldi, Aldri; Embi, Muhamad Ali; Saputra, Boni (Jurnal Studi Pemerintahan, 2024)
Every government agency that provides public services to the community must be able to produce quality public services that satisfy the community. It cannot be denied that the manager's duties cannot be separated from community satisfaction. Thus, this research aims to examine how the manager's function influences people's happiness in public service malls in Payakumbuh City, with special emphasis on the manager's internal and external responsibilities. This research uses an associative quantitative approach, supported by primary and secondary data, as well as validated and reliable field data collection questionnaires. Using the Slovin formula to calculate the sample size, 209 respondents were used in the proportional stratified random sampling procedure to obtain the sample size. Next, multiple regression analysis was used to evaluate the data, after previously passing a preparatory test called the classical assumption test. The findings of the analysis show that the role of managers, both internal and external, has been shown to have a major impact on people's satisfaction, sometimes simultaneously. Therefore, public service malls need to consider the various contributions made by managers to increase customer satisfaction.